Making work visible ethnographically grounded case studies of work practice - Szymanski, Margaret H.; Whalen, Jack, 1949- (Learning in doing., 2011)
"In the 1970s, Xerox pioneered the involvement of social science researchers in technology design and in developing better ways of working. The Xerox legacy is a hybrid methodology that combines an ethnographic interest in direct observation in settings of interest with an ethnomethodological concern to make the study of interactional work an empirical, investigatory matter. This edited volume is an overview of Xerox's social science tradition. It uses detailed case studies that show how the client engagement was conducted over time and how the findings were consequential for business impact. Case studies in retail, production, office, and home settings cover four topics: practices around documents, the customer front, learning and knowledge-sharing, and competency transfer. The impetus for this book was a 2003 Xerox initiative to transfer knowledge about how to conduct ethnographically grounded work-practice studies to its consultants so that they may generate the kinds of knowledge generated by the researchers themselves"--